Multi-channel polypyrrole / graphene-based Au nano composite capacitor material
By using multi-channel polypyrrole/reduced graphene oxide-based carrier in supercapacitor electrode materials and loading gold nanoparticles, the shortcomings of existing electrode materials in cyclic stability and electrochemical performance are solved, and high specific capacitance, stability and low-cost electrode material preparation are achieved.
Patent Information
- Application Number
- CN202411896509.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-25
AI Technical Summary
The existing supercapacitor electrode materials have shortcomings in cyclic stability and electrochemical performance, and the composite material preparation process is complex, cost is high, and performance is unstable.
A multi-channel polypyrrole/reduced graphene oxide-based carrier is used and gold nanoparticles are loaded to form nanocomposite capacitance materials with high porosity and multi-channel structures through specific preparation methods.
The specific capacitance performance, cyclic stability and conductivity of the electrode material are significantly improved, the preparation cost is reduced, and the stability of the material performance is improved.
Smart Images

Figure CN119694804A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a multi-channel polypyrrole / graphene-based Au nanocomposite capacitor material, belonging to the technical field of capacitor materials. Background Art
[0002] With the rapid development of economy, energy demand is growing continuously, and the traditional energy structure can no longer meet the needs of sustainable development. The research and development of new energy materials has become the focus of attention in today's world. As a green, efficient and renewable energy storage and conversion device, supercapacitors have the advantages of high power density, fast charging and discharging speed, and long cycle life. They have broad application prospects in mobile communications, electric vehicles, renewable energy and other fields. Among them, electrode materials are the key components of supercapacitors, and their performance directly determines the overall performance of supercapacitors.
[0003] In recent years, conductive polymers, carbon materials and their composites have attracted much attention in the research of supercapacitor electrode materials due to their excellent electrochemical properties. Conductive polymers such as polyaniline, polypyrrole, polythiophene, etc., occupy an important position in the research of supercapacitor electrode materials due to their unique pseudocapacitive properties, easy synthesis and processing. Polypyrrole (PPy), as a typical conductive polymer, has good electrochemical activity and conductivity, but its cycle stability and electrochemical performance still need to be further improved. Carbon materials are widely used as supercapacitor electrode materials due to their high specific surface area, good conductivity and stable chemical properties. Among them, the research on materials such as activated carbon, carbon nanotubes, and graphene is the most active. Graphene, as a two-dimensional material composed of a single layer of carbon atoms, has an extremely high theoretical specific surface area (up to 2630m
[0004] / g) and excellent electron transport properties, it is considered to be an ideal choice for supercapacitor electrode materials. However, graphene has problems such as poor dispersibility and insufficient electrochemical stability in practical applications, which limits its full performance. In order to overcome the limitations of a single material, researchers have begun to try to combine different types of materials to optimize performance. Composite materials combine the advantages of each component material and improve the comprehensive performance of electrode materials through synergistic effects. For example, the composite of conductive polymers and graphene-based materials can simultaneously improve the specific capacity, conductivity and cycle stability of electrode materials. On this basis, loading metal nanoparticles with high electrochemical reaction rates will further optimize the electrochemical properties of electrode materials. Gold nanoparticles (AuNPs) show great application potential in supercapacitor electrode materials due to their unique physicochemical properties, such as high specific surface area, excellent conductivity and catalytic activity. The introduction of gold nanoparticles can effectively improve the charge storage capacity and electrochemical reaction rate of electrode materials, thereby improving the overall performance of supercapacitors.
[0005] Based on the above background, the development of polypyrrole / graphene-based carriers and loading of metal nanomaterials is expected to combine the pseudocapacitive properties of polypyrrole, the high specific surface area of graphene-based materials and the excellent conductivity of metal nanoparticles, and through reasonable material design and preparation process, achieve a comprehensive improvement in specific capacity, cycle stability, conductivity and other aspects of electrode materials. However, current research still has certain limitations, such as complex preparation process of composite materials, high cost, unstable performance and other problems. Therefore, further optimization of preparation process, reduction of cost and improvement of material performance are important directions for future research. Summary of the invention
[0006] The present invention provides a multi-channel polypyrrole / graphene-based Au nanocomposite capacitor material, which can effectively solve the above problems.
[0007] The present invention is achieved in that:
[0008] A multi-channel polypyrrole / graphene-based Au nanocomposite capacitor material, the preparation method of which is as follows: putting graphene oxide powder into a container, adding water to stir and disperse, then adding FeCl3 solution and concentrated H3PO4, and continuing to stir and react for 25-35 minutes; adding the first batch of pyrrole monomers, reacting for 25-35 minutes, so that the pyrrole monomers are polymerized on the surface of graphene oxide under the action of FeCl3 to form a uniform polypyrrole PPy film layer, and at the same time, the graphene oxide is curled in three-dimensional space to form a multi-channel composite carrier; continuing to add the second batch of pyrrole monomers and HAuCl4 solution, and continuing to stir and react for 25-35 minutes. After 25-35 minutes, the unreacted pyrrole monomers are enriched in the three-dimensional space channels formed by the graphene oxide and the PPy film layer, and the HAuCl4 solution is reduced to gold nanoparticles loaded on the PPy surface; then, a H3PO4 solution containing ammonium persulfate is added dropwise, and the reaction is stirred for 50-70 minutes to polymerize the remaining pyrrole monomers in the three-dimensional space channels into PPy, and the filtered product is washed with water and ethanol. The obtained filtered product is stirred in a H3PO4 solution containing antioxidant hemic acid overnight, filtered again, and the filtered product is washed with water and anhydrous ethanol, and naturally dried to obtain a product powder.
[0009] In some embodiments, in the multi-channel polypyrrole / graphene-based Au nanocomposite capacitor material, the mass contents of PPy, rGO and Au in the composite capacitor material are 45-55%, 45-55% and 0.4-0.8%, respectively.
[0010] In some embodiments, the method for preparing the multi-channel polypyrrole / graphene-based Au nanocomposite capacitor material is characterized by comprising the following steps:
[0011] S1, put graphene oxide powder into a container, add water and stir to disperse, then add FeCl3 solution and concentrated H3PO4, and continue stirring to react for 25-35 minutes;
[0012] S2, adding the first batch of pyrrole monomers and reacting for 25-35 minutes, so that the pyrrole monomers are polymerized on the surface of graphene oxide under the action of FeCl3 to form a uniform polypyrrole PPy film layer, and at the same time, the graphene oxide is curled in three-dimensional space to form a multi-channel composite carrier;
[0013] S3, continue to add the second batch of pyrrole monomer and HAuCl4 solution, and continue to stir and react for 25-35 minutes, the unreacted pyrrole monomer is enriched in the three-dimensional space channel formed by the graphene oxide and the PPy film layer, and the HAuCl4 solution is reduced to gold nanoparticles loaded on the PPy surface;
[0014] S4, then, dropwise add H3PO4 solution containing ammonium persulfate, stir and react for 50-70 minutes to polymerize the remaining pyrrole monomers in the three-dimensional space channel into PPy, filter, wash the filtered product with water and ethanol, stir the obtained filtered product in H3PO4 solution containing antioxidant acid overnight, filter again, wash the filtered product with water and anhydrous ethanol, and dry naturally to obtain the product powder.
[0015] In some embodiments, the concentration of the FeCl3 solution is 0.08-0.12 M, and the concentration of the HAuCl4 solution is 22-25 m M; the usage ratio of the graphene oxide powder, the FeCl3 solution, the first batch of pyrrole monomers, the second batch of pyrrole monomers, and the HAuCl4 solution is 45-55 mg: 80-120 μL: 45-55 μL: 120-170 μL: 0.40-0.55 mL.
[0016] In some embodiments, the H3PO4 solution containing ammonium persulfate is prepared by dissolving 0.5-0.7 g / mL ammonium persulfate in a 10 wt % H3PO4 solution.
[0017] In some embodiments, the H3PO4 solution containing hematoxylin is prepared by dissolving 80-120 mM hematoxylin in a 2 wt % H3PO4 solution.
[0018] A method for preparing a capacitor electrode, using Nafion as a binder, loading the multi-channel polypyrrole / graphene-based Au nanocomposite capacitor material on the surface of a glassy carbon electrode, thereby preparing the capacitor electrode.
[0019] A capacitor electrode prepared by the above method.
[0020] An electrochemical testing method for a capacitor electrode, using the capacitor electrode as a working electrode, a graphite electrode as an auxiliary electrode, a saturated calomel electrode (SCE) as a reference electrode, and an electrochemical workstation to perform a cyclic voltammetry (CV) test and a constant current charge and discharge (GCD) test in a Na2SO4 solution, wherein the CV test voltage range is -0.5V-0.5V, and the GCD test current density is 2-20A / g.
[0021] A supercapacitor is made from the multi-channel polypyrrole / graphene-based Au nanocomposite capacitor material.
[0022] The beneficial effects of the present invention are:
[0023] The capacitor electrode material of the present invention, its core is to adopt the polypyrrole / reduced graphene oxide composite material with high porosity and multi-channel structure as carrier.On this basis, further load gold nanoparticles, thereby prepare a kind of polypyrrole / reduced graphene oxide / gold (PPy / rGO / Au) nanocomposite capacitor material with excellent performance.This composite material not only has significant advantages in structure, but also performs well in electrochemical performance, is embodied in its higher specific capacitance performance.Through this unique design, this capacitor electrode material can provide more active sites in electrochemical reaction, thereby significantly improve its capacitance performance, make it have a wide range of application prospects in energy storage and conversion field. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.
[0025] Figure 1 SEM images of the morphology and structure of PPy (a), PPy / rGO (b), PPy / Au (c) and PPy / rGO / Au (d).
[0026] Figure 2 CV curves of PPy (a), PPy / rGO (b), PPy / Au (c) and PPy / rGO / Au (d) in 1 M Na2SO4 solution at different scanning speeds.
[0027] Figure 3 This is the CV curve of PPy / rGO / Au series electrodes in 1M Na2SO4 solution.
[0028] Figure 4This is the relationship curve between specific capacity and scan rate when the PPy / rGO / Au series electrodes were subjected to CV test in 1M Na2SO4 solution.
[0029] Figure 5 GCD curves of PPy (a), PPy / rGO (b), PPy / Au (c), and PPy / rGO / Au (d) at different current densities in 1 M Na2SO4 solution.
[0030] Figure 6 This is the GCD curve of the PPy / rGO / Au series electrodes at a current density of 2A / g in 1M Na2SO4 solution.
[0031] Figure 7 The relationship curve between energy density and current density when the PPy / rGO / Au series electrodes were tested by GCD in 1M Na2SO4 solution. DETAILED DESCRIPTION
[0032] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention. Therefore, the following detailed description of the embodiments of the present invention provided in the drawings is not intended to limit the scope of the invention claimed for protection, but merely represents the selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0033] Example 1 Preparation of PPy / rGO / Au powder
[0034] Take 50mg GO powder and put it into a 250mL flat-bottom flask, then add 50mL pure water and stir until the powder is evenly dispersed. Next, add 100μL 0.1M FeCl3 solution and 2mL concentrated H3PO4 to the flask, and continue to stir the mixture for half an hour. After completing this step, add 50μL pyrrole monomer to the mixed solution and react for half an hour so that the low concentration of pyrrole monomer polymerizes on the surface of graphene oxide under the action of FeCl3 to form a uniform PPy film layer. This step also makes the graphene oxide curl in three-dimensional space to form a multi-channel composite carrier. Then, 150 μL of pyrrole monomer and 0.45 mL of 24.28 mM HAuCl4 solution were added, and stirring was continued for one and a half hours to allow the unreacted pyrrole monomer to be enriched in the three-dimensional space channel formed by the graphene oxide and the PPy thin layer; at this time, the HAuCl4 solution was adsorbed on the graphene oxide and the PPy thin layer, and coordinated with part of the pyrrole monomer, reduced to gold nanoparticles and enriched in the three-dimensional space channel formed by the graphene oxide and the PPy thin layer. Take 0.3 g of ammonium persulfate and add it to 5 mL of 10 wt% H3PO4 solution. After it is completely dissolved, it is slowly added dropwise to the above solution, stirred and reacted for 1 hour, so that the remaining pyrrole monomer in the three-dimensional channel is polymerized into PPy, filtered, washed with water and ethanol, and the obtained powder was stirred overnight in 50 mL of 2 wt% H3PO4 solution containing 100 mM anti-hemolytic acid. The product was filtered, washed with water and anhydrous ethanol, and dried naturally to obtain the product powder. The mass contents of PPy, rGO and Au in the composite are 50.8%, 48.6% and 0.6%, respectively.
[0035] Comparative Example 1 Preparation of PPy powder
[0036] Add 100 μL of 0.1 mol / L FeCl3 solution, 2 mL of concentrated H3PO4 and 50 mL of pure water into a 250 mL flat-bottom flask and stir for 0.5 h. Add 200 μL of pyrrole monomer to the mixed solution and stir for 2 h. Add 0.3 g of ammonium persulfate to 5 mL of 10 wt% H3PO4, and after the solution is mixed, slowly drip it into the solution prepared in the previous step, stir for 1 h and filter. Wash the filtered product with water and anhydrous ethanol, add it to 50 mL of 2 wt% H3PO4 (containing 100 mM sodium hypochlorite) and stir for 24 h to remove Fe in the mixed solution. 3+ The product was filtered, washed with water and anhydrous ethanol, and dried naturally to obtain PPy powder.
[0037] Comparative Example 2 Preparation of PPy / rGO powder
[0038] First, take 50mg of graphene oxide (GO) powder and put it into a 250mL flat-bottom flask, then add 50mL of pure water and stir until the powder is evenly dispersed. Then, add 100μL of 0.1M FeCl3 solution and 2mL of concentrated H3PO4 to the flask, and continue to stir the mixture for half an hour. After completing this step, add 50μL of pyrrole monomer to the mixed solution, react for half an hour to make the low concentration of pyrrole monomer polymerize on the surface of graphene oxide under the action of FeCl3 to form a uniform PPy film layer. This step also makes graphene oxide curl up in three-dimensional space to form a multi-channel composite carrier. Then continue to add 150μL of pyrrole monomer, and continue to stir for one and a half hours so that the unreacted pyrrole monomer is enriched in the three-dimensional space channel formed by graphene oxide and PPy thin layer. Then prepare a solution containing 5mL of 10wt% H3PO4 and add 0.3g of ammonium persulfate to it. After it is completely dissolved, slowly add this solution dropwise to the mixed solution prepared previously and stir for 1h. Then filter the mixture and wash the filtered product with water and anhydrous ethanol. Add it to 50mL of 2wt% H3PO4 (containing 100mM sodium hypochlorite) and stir for 24h to remove Fe in the mixed solution. 3+ Finally, the product was filtered and washed again with water and anhydrous ethanol. The washed product was placed in suitable conditions and dried naturally to finally obtain PPy / rGO powder with a component mass ratio of 4:1.
[0039] Comparative Example 3 Preparation of PPy / Au powder
[0040] First, add 100μL of 0.1mol / L FeCl3 solution, 2mL of concentrated H3PO4, 0.45mL of 24.28mM HAuCl4 solution and 50mL of pure water to a 250mL flat-bottom flask and continue stirring for 0.5h. Subsequently, add 200μL of pyrrole monomer to the mixed solution and continue stirring for 2h. Next, take 5mL of 10wt% H3PO4 solution, add 0.3g of ammonium persulfate 8, and continue stirring until the solution is completely mixed. Subsequently, the mixed solution is gradually added to the previously prepared mixed solution, stirring for 1h. After stirring is completed, filter. Wash the filtered material with water and anhydrous ethanol, and add the washed product to 50mL 2wt% H3PO4 solution containing 100mM anti-hemolytic acid, and continue stirring for 24h to remove Fe in the mixed solution. 3+ The product was filtered again, and washed with water and anhydrous ethanol until it was naturally dried, and finally PPy / Au powder was obtained, with the mass contents of PPy and Au being 98.9% and 1.1%, respectively.
[0041] Test Case
[0042] Using Nafion as a binder, the powder materials prepared in Example 1 and Comparative Examples 1-3 were loaded on a 5 mm glassy carbon electrode surface to prepare capacitor electrodes, a graphite electrode was selected as an auxiliary electrode, and a saturated calomel electrode (SCE) was used as a reference electrode. Using an electrochemical workstation (CHI660D), cyclic voltammetry (CV) and constant current charge and discharge (GCD) tests were performed on the PPy-based series electrode materials in 1M Na2SO4 solution. The CV test voltage range was -0.5V to 0.5V (vs. SCE), and the current density of the GCD test was 2 to 20A / g. The test results are shown in Table 1.
[0043] Table 1 Specific capacitance and energy density of PPy / rGO / Au series electrodes
[0044]
[0045]
[0046] Results and Discussion
[0047] Figure 1 This is the SEM image of the prepared material. Figure 1 (a) It can be seen that the prepared PPy is irregular spherical particles of 200-300 nm, and the particles are well dispersed and have a high porosity. Figure 1 As can be seen in (b), when PPy is composited with rGO, PPy grows on the surface of rGO and causes rGO to form a wrinkled structure in three-dimensional space, thereby forming more spatial channels, which can effectively increase the surface area of the composite material and facilitate the diffusion of the electrolyte on the electrode surface; in addition to polymerizing on the rGO surface to form a uniform film layer, PPy also partially polymerizes into irregular spherical particles and is loaded in the three-dimensional spatial channels formed by PPy / rGO. Figure 1 (a) Compared with Figure 1 The PPy particles in (b) are reduced in size to about 100-200 nm. Figure 1 (c) It can be found that after being composited with Au, the size of PPy particles is reduced to about 100-200 nm without changing the porosity of PPy particles, and Au nanoparticles are deposited on the surface of these PPy particles. Figure 1 (d) It can be observed that in the PPy / rGO / Au composite, Figure 1(b) Similarly, when PPy is compounded with rGO, PPy grows on the surface of rGO and causes rGO to form a wrinkled structure in three-dimensional space, thereby forming more spatial channels. After compounding with Au, the size of the nanoparticles loaded in the three-dimensional spatial channels of PPy / rGO is further reduced to about 50-100nm, thus forming a PPy / rGO / Au composite material with high porosity and multiple three-dimensional spatial channels.
[0048] exist Figure 2 In the figure, the CV curves of PPy, PPy / rGO, PPy / Au and PPy / rGO / Au at different scan rates in 1M Na2SO4 solution are presented. By observing these curves, it can be clearly observed that with the increase of the cyclic voltammetry scan rate, the response current density of all electrode materials also shows an increasing trend. By comparing these four figures, we can find that the current density of PPy is the lowest. When PPy forms a binary composite material with Au or rGO, its current density is improved. In particular, when Au and rGO are simultaneously compounded into PPy, the current density is significantly enhanced. These results show that after the introduction of Au and rGO, the prepared ternary composite material exhibits excellent capacitive performance. The reason can be attributed to the good synergistic effect between the three-dimensional spatial channels on the surface of PPy / rGO and the high-porosity PPy / Au pseudocapacitive material. At the same time, the large surface area and void structure of PPy / rGO are conducive to the transmission of electrolyte ions at high current density.
[0049] Figure 3 The CV curves of different composite materials at a scan rate of 50mV / s in 1M Na2SO4 solution are compared. At a voltage of 0.2V, the current density of the PPy / rGO / Au electrode material reaches 12A / g, while the current densities of the other three electrode materials are 6A / g, 6A / g and 6.5A / g, respectively. Compared with PPy, the current density of the binary composite material has not been significantly improved, but the current density of the PPy / rGO / Au ternary composite electrode material is twice that of PPy, which clearly shows that the capacitive performance of the PPy / rGO / Au ternary composite electrode has been significantly improved.
[0050] Figure 4The relationship curve between specific capacity and scan rate obtained by CV test of the prepared material in 1M Na2SO4 solution is shown. According to the data in the figure, when the scan rate is 5mV / s, the specific capacitance of PPy reaches 115F / g. Compared with PPy, the specific capacitance of the electrode material composited with rGO is increased to 135F / g, an increase of 17.4%; and the specific capacitance of the electrode material composited with Au is further increased to 145F / g, an increase of 26.1%. When the electrode material is composited with rGO and Au at the same time, the specific capacitance is significantly increased to 220F / g, an increase of 91.3%.
[0051] Figure 5 The GCD curve of the prepared material at a current density of 2 to 20 A / g in a 1M Na2SO4 solution is shown. This figure shows the advantages of PPy / rGO / Au materials in terms of capacitance performance. It can be observed from the GCD curve that PPy has the shortest single charge and discharge time. In contrast, the charge and discharge time of materials composited with rGO or Au is extended, especially for electrode materials composited with rGO and Au at the same time, the increase in charge and discharge time is most significant. Obviously, the large number of surface wrinkles and three-dimensional spatial channels brought by PPy / rGO to the capacitor material system, as well as the enhancement of the conductivity and capacitance properties of the capacitor material by the high porosity PPy / Au, greatly enhance the capacitance performance of the composite system.
[0052] Figure 6 The GCD curve of the prepared material at a current density of 2A / g in a 1M Na2SO4 solution is shown. It can be seen from the figure that under the condition of 2A / g, the single charge and discharge time of PPy is 100s. When PPy is composited with rGO, the single charge and discharge time is extended to 118s, and when composited with Au, the single charge and discharge time is further extended to 138s, an increase of 18% and 38%, respectively. Although these improvements are positive, their advantages are not very significant. However, when PPy is composited with rGO and Au at the same time, the single charge and discharge time is greatly increased to 216s, reaching 2.16 times that of the original PPy, indicating that the PPy / rGO / Au ternary composite material has better capacitance performance.
[0053] Figure 7 The relationship curve between specific capacity and current density obtained by GCD test of the prepared material in 1M Na2SO4 solution is shown. At a current density of 2A / g, the energy density of the PPy electrode material is 12.5Wh / kg. When PPy is compounded with rGO or Au, the energy density of the formed PPy / rGO and PPy / Au binary composite electrode materials is increased to 15Wh / kg and 16Wh / kg respectively. The energy density of the PPy / rGO / Au ternary composite electrode material is increased to 27Wh / kg.
[0054] Table 1 clearly shows the specific capacitance and energy density data of the prepared materials. Under the condition of a scan speed of 5mV / s, the specific capacitance of the electrode material of PPy composited with rGO or Au increased by 17.4% and 26.1%, respectively, while the specific capacitance of the electrode material of PPy composited with rGO and Au increased by 91.3%. The data clearly show the large number of surface wrinkles and three-dimensional space channels brought by PPy / rGO to the capacitor material system, as well as the enhancement of the conductivity and capacitance properties of the capacitor material by high porosity PPy / Au, which effectively enhances the specific capacitance of the composite system. At a current density of 2A / g, it can be seen that after PPy is composited with rGO or Au, the energy density of the electrode material is increased by 20% and 28%, respectively, while after being composited with rGO and Au at the same time, the energy density is increased by 116%. This data once again confirms that the synergistic effect between PPy, rGO and Au can effectively improve the capacitance performance of the electrode material.
[0055] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A multi-channel polypyrrole / graphene-based Au nanocomposite capacitor material, characterized in that: The preparation method is as follows: putting graphene oxide powder into a container, adding water to stir and disperse, then adding FeCl3 solution and concentrated H3PO4, and continuing to stir and react for 25-35 minutes; adding the first batch of pyrrole monomers, reacting for 25-35 minutes, so that the pyrrole monomers are polymerized on the surface of graphene oxide under the action of FeCl3 to form a uniform PPy film layer, and at the same time, the graphene oxide is curled in three-dimensional space to form a multi-channel composite carrier; continuing to add the second batch of pyrrole monomers and HAuCl4 solution, and continuing to stir and react for 25-35 minutes, and the unreacted The pyrrole monomers are enriched in the three-dimensional space channels formed by the graphene oxide and the PPy film layer, and the HAuCl4 solution is reduced to gold nanoparticles loaded on the PPy surface; then, a H3PO4 solution containing ammonium persulfate is added dropwise, and the reaction is stirred for 50-70 minutes to polymerize the remaining pyrrole monomers in the three-dimensional space channels into PPy, and the filtered product is washed with water and ethanol. The obtained filtered product is stirred in a H3PO4 solution containing antioxidant acid overnight, and then filtered again, and the filtered product is washed with water and anhydrous ethanol, and naturally dried to obtain the product powder.
2. The multi-channel polypyrrole / graphene-based Au nanocomposite capacitor material according to claim 1, characterized in that: in, The mass contents of PPy, rGO and Au in the composite capacitor material are 45-55%, 45-55% and 0.4-0.8% respectively.
3. A method for preparing the multi-channel polypyrrole / graphene-based Au nanocomposite capacitor material according to claim 1 or 2, characterized in that: The following steps are involved: S1, put graphene oxide powder into a container, add water and stir to disperse, then add FeCl3 solution and concentrated H3PO4, and continue stirring to react for 25-35 minutes; S2, adding the first batch of pyrrole monomers and reacting for 25-35 minutes, so that the pyrrole monomers are polymerized on the surface of graphene oxide under the action of FeCl3 to form a uniform PPy film layer, and at the same time, the graphene oxide is curled in three-dimensional space to form a multi-channel composite carrier; S3, continue to add the second batch of pyrrole monomer and HAuCl4 solution, and continue to stir and react for 25-35 minutes, the unreacted pyrrole monomer is enriched in the three-dimensional space channel formed by the graphene oxide and the PPy film layer, and the HAuCl4 solution is reduced to gold nanoparticles loaded on the PPy surface; S4, then, dropwise add H3PO4 solution containing ammonium persulfate, stir and react for 50-70 minutes to polymerize the remaining pyrrole monomers in the three-dimensional space channel into PPy, filter, wash the filtered product with water and ethanol, stir the obtained filtered product in H3PO4 solution containing antioxidant acid overnight, filter again, wash the filtered product with water and anhydrous ethanol, and dry naturally to obtain the product powder.
4. The preparation method according to claim 3, characterized in that: The concentration of the FeCl3 solution is 0.08-0.12M, and the concentration of the HAuCl4 solution is 22-25mM; the usage ratio of the graphene oxide powder, the FeCl3 solution, the first batch of pyrrole monomers, the second batch of pyrrole monomers, and the HAuCl4 solution is 45-55mg:80-120μL:45-55μL:120-170μL:0.40-0.55mL.
5. The preparation method according to claim 3, characterized in that: The H3PO4 solution containing ammonium persulfate is prepared by dissolving 0.5-0.7 g / mL of ammonium persulfate in a 10 wt% H3PO4 solution.
6. The preparation method according to claim 3, characterized in that: The H3PO4 solution containing hemic acid is prepared by dissolving 80-120 mM hemic acid in a 2 wt% H3PO4 solution.
7. A method for preparing a capacitor electrode, characterized in that: The capacitor electrode is prepared by using Nafion as a binder and loading the multi-channel polypyrrole / graphene-based Au nanocomposite capacitor material according to claim 1 or 2 on the surface of a glassy carbon electrode.
8. A capacitor electrode prepared by the method of claim 7.
9. An electrochemical testing method for a capacitor electrode according to claim 8, characterized in that: The capacitor electrode is used as the working electrode, the graphite electrode is used as the auxiliary electrode, and the saturated calomel electrode SCE is used as the reference electrode. An electrochemical workstation is used to carry out cyclic voltammetry (CV) test and constant current charge and discharge (GCD) test in a Na2SO4 solution. The CV test voltage range is -0.5V-0.5V, and the current density of the GCD test is 2-20A / g.
10. A supercapacitor, characterized in that: It is made from the multi-channel polypyrrole / graphene-based Au nanocomposite capacitor material according to claim 1 or 2.